Lim ( căn bậc 3 của 2x+1 ) – 1 )/x-1 khi x tiến tới 1

Question

Lim ( căn bậc 3 của 2x+1 ) – 1 )/x-1 khi x tiến tới 1

in progress 0
Reese 4 ngày 2021-12-06T23:49:27+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-12-06T23:51:04+00:00

    Đáp án:

    \[\mathop {\lim }\limits_{x \to 1} \frac{{\sqrt[3]{{2x – 1}} – 1}}{{x – 1}} = \frac{2}{3}\]

    Giải thích các bước giải:

     Ta có:

    \(\begin{array}{l}
    \mathop {\lim }\limits_{x \to 1} \frac{{\sqrt[3]{{2x – 1}} – 1}}{{x – 1}}\\
     = \mathop {\lim }\limits_{x \to 1} \frac{{\left( {\sqrt[3]{{2x – 1}} – 1} \right)\left( {{{\sqrt[3]{{2x – 1}}}^2} + \sqrt[3]{{2x – 1}}.1 + {1^2}} \right)}}{{\left( {x – 1} \right).\left( {{{\sqrt[3]{{2x – 1}}}^2} + \sqrt[3]{{2x – 1}}.1 + {1^2}} \right)}}\\
     = \mathop {\lim }\limits_{x \to 1} \frac{{{{\sqrt[3]{{2x – 1}}}^3} – {1^3}}}{{\left( {x – 1} \right).\left( {{{\sqrt[3]{{2x – 1}}}^2} + \sqrt[3]{{2x – 1}} + 1} \right)}}\\
     = \mathop {\lim }\limits_{x \to 1} \frac{{\left( {2x – 1} \right) – 1}}{{\left( {x – 1} \right)\left( {{{\sqrt[3]{{2x – 1}}}^2} + \sqrt[3]{{2x – 1}} + 1} \right)}}\\
     = \mathop {\lim }\limits_{x \to 1} \frac{{2\left( {x – 1} \right)}}{{\left( {x – 1} \right)\left( {{{\sqrt[3]{{2x – 1}}}^2} + \sqrt[3]{{2x – 1}} + 1} \right)}}\\
     = \mathop {\lim }\limits_{x \to 1} \frac{2}{{{{\sqrt[3]{{2x – 1}}}^2} + \sqrt[3]{{2x – 1}} + 1}}\\
     = \frac{2}{{{{\sqrt[3]{{2.1 – 1}}}^2} + \sqrt[3]{{2.1 – 1}} + 1}}\\
     = \frac{2}{3}
    \end{array}\)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )